2015
DOI: 10.1016/j.socscimed.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

International migration of health professionals and the marketization and privatization of health education in India: From push–pull to global political economy

Abstract: Health worker migration theories have tended to focus on labour market conditions as principal push or pull factors. The role of education systems in producing internationally oriented health workers has been less explored. In place of the traditional conceptual approaches to understanding health worker, especially nurse, migration, I advocate global political economy (GPE) as a perspective that can highlight how educational investment and global migration tendencies are increasing interlinked. The Indian case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 33 publications
1
52
1
Order By: Relevance
“…Many nurses working in private hospitals had trained as nurses with a view to migration, either to the Indian metropolises, the Gulf or (eventually) to the UK, USA, Australia or Canada (Nair 2012, Walton-Roberts 2015.…”
Section: But Doctors Are Always Against Them Doctors Want Nurses To mentioning
confidence: 99%
See 2 more Smart Citations
“…Many nurses working in private hospitals had trained as nurses with a view to migration, either to the Indian metropolises, the Gulf or (eventually) to the UK, USA, Australia or Canada (Nair 2012, Walton-Roberts 2015.…”
Section: But Doctors Are Always Against Them Doctors Want Nurses To mentioning
confidence: 99%
“…The general policy of a diminution in regulation had meant that it was possible for private schools of nursing to be established -in Kerala, and the other southern states of India. These number in the hundreds, often charge extortionate fees, provide a highly variable standard of education and exist in a context where regulation is deemed to be weak and ineffective (Walton-Roberts 2015 The rapid growth of private sector nurse education (Walton-Roberts 2015), a response to globalisation, has been problematic for the state regulators of nursing in India, who have often been unable or unwilling to enforce educational standards in the private sector schools of nursing. Some interviewees were dubious about the quality of the training nursing students in private colleges received:…”
Section: Directorate Of Medical Education) Nursing Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Among the prominent reason for this are pursuit of higher education, financial incentives, congruence of Indian medical training with Western methods due to colonial link and material benefits with improvement of working conditions and facilities. 38,39 Though these migrated physicians form a backbone of National Health system in western countries, for developing and under developed nations it is a matter of significant concern in terms of both, loss of skilled manpower and wasteful utilisation of scarce resources. 40,41 Contrary to that reported by Kaushik et al, our study showed doctor external migration of 9%, with majority of them leaving India just after graduation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the geography of SHW migration circuits demands further analysis at the regional scale, where border regions and emerging global health service centres have acquired significance (Bochaton, 2014;Glinos and Baeten, 2014). This regional focus also draws attention to the links between health system change and SHW training and migration circuits, which are constantly negotiated, especially in light of international migration opportunities (Walton-Roberts, 2015). Health geographers could make considerable research contributions in such areas.…”
Section: Geographies Of International Shw Circulation: Care Chains Anmentioning
confidence: 99%